2016
DOI: 10.1080/23311916.2016.1178626
|View full text |Cite
|
Sign up to set email alerts
|

Surface quality of marble machined by abrasive water jet

Abstract: This paper presents a study conducted to examine the effect of cutting parameters, namely standoff distance, nozzle traverse speed (TS), abrasive flow rate (AFR), and material type on cutting performance for two types of marble workpieces, Carrara white and Indian green. Statistical analysis was undertaken to assess the influence of the cutting parameters on the process performances in terms of surface roughness, surface waviness, and Kerf taper ratio. The results showed that the TS and material type were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Under normal conditions, this value is lower, which means that the method of machining materials being discussed may be considered as relatively accurate. Given the above, AWJ, which is a universal technological tool, provides itself with a wider range of machining applications, enabling the shaping of many types of materials, such as metals and its alloys [ 14 , 15 , 16 , 17 , 18 , 19 ], ceramic, glass [ 20 ], composites [ 21 , 22 ], flammable materials, leather, and natural stone-based materials [ 23 ], as well as regenerating the cutting ability of grinding tools [ 24 ]. Nevertheless, there is still a need for further research related to this technology in order to increase the efficiency of material machining.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, this value is lower, which means that the method of machining materials being discussed may be considered as relatively accurate. Given the above, AWJ, which is a universal technological tool, provides itself with a wider range of machining applications, enabling the shaping of many types of materials, such as metals and its alloys [ 14 , 15 , 16 , 17 , 18 , 19 ], ceramic, glass [ 20 ], composites [ 21 , 22 ], flammable materials, leather, and natural stone-based materials [ 23 ], as well as regenerating the cutting ability of grinding tools [ 24 ]. Nevertheless, there is still a need for further research related to this technology in order to increase the efficiency of material machining.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in industries due to its several advantages on other unconventional machines such as high material removal rate, no thermal effect, minimal stresses, no chatter and high flexibility. AWJM process is suitable for machining composites [1]. Carbon fibre vinyl ester composite is used in aerospace industries, automotive industries, sport goods, marine vehicle and pressure vessel parts because of its durability, high strength to weight ratio, and good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Abrasive embedment was prominent in samples cut with high abrasive mass flow rate and low stand-off distance. Abdullah et al [1] studied surface quality of marble machined by AWJM and it was found that the nozzle traverse speed is the most significant factor followed by standoff distance. Dhanawade and Kumar [11] concluded that AWJM is the most developed and effective machining for fiber reinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The AWJC method cuts effectively almost all engineering materials and thicknesses such as aluminium [40], titanium alloys [41], glass [42], brass, pre-hardened steel, tool steel [43], stainless steel, mild steel [44], copper, plastic, quartz, ceramic [45], laminates, composites [46], flammable materials, leather, stone [47], granite, marble [48], foam, Inconel, fish, meat, etc. [49].…”
Section: Applicationsmentioning
confidence: 99%